Efficacy and safety of hyaluronic-polidocanol foam in sclerotherapy for head and neck venous malformations - Sun, Zhaoyang; Liu, Yiran; Chen, Anwei; Wang, Tao; Liu, Shaohua (Frontiers in Neurology, 2024)
Background Foam sclerotherapy is currently the first-line treatment for venous malformations (VMs). Hyaluronic acid-polidocanol (HA-POL) foam has been used in the treatment of head and neck VMs recently; however, its clinical efficacy and safety have yet to be further evaluated, and the impact of age and other related factors on its safety is still unclear. Objective To assess the efficacy and safety of HA-POL foam in the treatment of head and neck VMs. Methods and materials We performed a single-center retrospective review of all patients with VMs involving the head and neck region undergoing HA-POL foam sclerotherapy from February 2015 to February 2022 in the Oral and Maxillofacial Surgery Department of Qilu Hospital Shandong University. Patients’ medical records were collected and all patients enrolled were followed up for 1–6 months (group 1), part of them were followed up for 3–9 years (group 2). Results A total of 223 patients with head and neck VMs were enrolled in the study, with 36 patients who were followed for 3–9 years. Total response rate in group 1 was 96.41% (n = 215), of which 30.94% (n = 69) of the patients met the criteria of “resolution,” and 65.47% (n = 146) of the patients had “significant improvement.” In group 2, the total response rate was 72.22% (n = 26), of which the rates of the patients met the criteria of “resolution” and patients had “significant improvement” were all 36.11% (n = 13)0.144 (64.57%) patients experienced complications like localized swelling, pain and fever, and no serious complications occurred. The risk of developing complications after treatment was independent of age, and was weakly associated with the dose of HA-POL foam. Conclusion The HA-POL foam sclerotherapy is safe and effective in the treatment of head and neck VMs.